Evaluation of the Clinical Performance of 7 Serological Assays for SARS-CoV-2 for Use in Clinical Laboratories. (17th May 2021) - Plaga, Alexis; Wei, Ruhan; Olson, Elizabeth; Payto, Drew; Harrington, John; Nwe-Kissig, Pyik That; Strizzi, Michelle; Zilka, Sarah; Ko, Jennifer; Colón-Franco, Jessica M
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) serological assays have emerged as a response to the global pandemic, warranting studies evaluating their clinical performance. This study investigated 7 commercially available SARS-CoV-2 serological assays in samples from noninfected individuals and hospitalized patients. Methods: SARS-CoV-2 qualitative serological assays by Abbott (IgG), Beckman (IgG), DiaSorin (IgG), EUROIMMUN (IgG and IgA), Roche and Bio-Rad (Total) were evaluated using specimens collected pre-December 2019 (n = 393), from nucleic acid amplification testing (NAAT) negative patients (n = 40), and from 53 patients with COVID-19 by NAAT collected 3–21 days post-onset of symptoms (POS) (N = 83). Negative agreement (NA), positive agreement (PA), and positive and negative predictive values (PPV and NPV) at prevalences of 5% and 10% were calculated. Results: The overall %NA; 95% CI in the negative samples were: Roche 99.8%; 99.3–100.2, Beckman 99.8%; 98.7–100.0, Abbott and Bio-Rad 99.3%; 98.0–99.9, DiaSorin 98.4; 97.2–99.6, EUROIMMUN IgG 97.5%; 95.5–98.7, and EUROIMMUN IgA 79.7%; 75.9–83.5), accounting for positive/equivocal results as false positives. The %PA; 95% CI in samples collected 14+ days POS (n = 24) were: Bio-Rad 83.3%; 68.4–98.2, Abbott and Roche 79.2%; 62.9–95.4, EUROIMMUN IgA 70.8%; 52.6–89.0, Beckman 58.3%; 38.6–78.1, DiaSorin 54.2; 34.2–74.1, and EUROIMMUN IgG 50.0%; 30.0–70.0, accounting for negative/equivocal results as false negatives. NPVs ranged from 97.4%–98.9% and 94.7%–97.7% for prevalences 5% and 10%, respectively. PPVs ranged from 15.5%–94.8% and 27.9%–97.4% for prevalences 5% and 10%, respectively. Conclusion: The Roche and Beckman assays resulted in fewer false positives, followed by the Bio-Rad and Abbott assays. While the Bio-Rad assay demonstrated higher antibody detection in COVID-19-positive patients, PA claims cannot be established with a high level of confidence in our sample population.